On the key role of SiO2@POSS hybrid filler in tailoring networking and interfaces in rubber nanocomposites. (February 2018) - Redaelli, Matteo; D'Arienzo, Massimiliano; Brus, Jiri; Di Credico, Barbara; Geppi, Marco; Giannini, Luca; Matejka, Libor; Martini, Francesca; Panattoni, Francesco; Spirkova, Milena; Šlouf, Miroslav; Scotti, Roberto; et al.
Abstract: The present study provides a comprehensive investigation at the micro and nanoscale of the interface between hybrid SiO2 @POSS nanofiller, where silica nanoparticles (NPs) and POSS nanocages are intimately interconnected, and Styrene Butadiene Rubber (SBR). SEM and AFM inspection and, more in depth, solid state 1 H NMR revealed a remarkable fraction of rigid rubber close to the SiO2 @POSS surfaces, which increases with the curing temperature. Instead, a reduced amount of immobilized rubber was detected for SBR/SiO2 +POSS nanocomposites, obtained by simply mixing SBR, SiO2 and POSS. The results allowed us to propose a model for the network formation in C-SBR/SiO2 @POSS. This is based on the progressive activation by dicumylperoxide (DCP) of the methacryl functionalities of POSS nanounits which, being closely connected to SiO2 NPs in SiO2 @POSS, promote crosslinking in proximity of the filler surfaces, and lead to the generation of a tight network strongly bonded to the rubber chains. Highlights: Effect of SiO2 @POSS nanofiller on the properties of SBR nanocomposites. Investigation at the micro and nanoscale. SEM, AFM and Solid 1 HNMR revealed a remarkable fraction of rigid rubber. Generation of a tight network strongly bonded to the rubber chains. Proposal of a model for the network formation.